1990
DOI: 10.1007/bf00177808
|View full text |Cite
|
Sign up to set email alerts
|

Skin necrosis and oral anticoagulant therapy: a review of the literature

Abstract: In spite of the wide use of oral anticoagulant therapy, skin necrosis remains an infrequent complication. A thorough search of the earlier scientific literature in English revealed sporadic cases that cannot supply enough data about the nature of this rare phenomenon. More current articles have examined this complication with recently developed and more sophisticated hematologic tests. A summary and analysis of all reported cases (a total of 105) were undertaken, in an attempt to find a common denominator that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Despite the widespread use of oral anticoagulant treatment, reports of skin necrosis are still unusual. Recent theories support the combined roles of local factors, a temporary unbalance of coagulation mechanisms, and genetic factor that determines a decreased level of (protein C and protein S), the two vitamin-K dependent glycoproteins that lead to a hypercoagulable state in the pathogenesis of cutaneous necrosis induced by oral anticoagulants [ 3 , 5 ]. Skin necrosis can result from endothelial damage and microthrombi development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the widespread use of oral anticoagulant treatment, reports of skin necrosis are still unusual. Recent theories support the combined roles of local factors, a temporary unbalance of coagulation mechanisms, and genetic factor that determines a decreased level of (protein C and protein S), the two vitamin-K dependent glycoproteins that lead to a hypercoagulable state in the pathogenesis of cutaneous necrosis induced by oral anticoagulants [ 3 , 5 ]. Skin necrosis can result from endothelial damage and microthrombi development.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports have described a late-onset presentation. Despite the lack of understanding of the pathogenesis of cutaneous necrosis, recent research has suggested that local and genetic factors, as well as a transient imbalance of coagulation mechanisms could play a role [ 3 ]. The most commonly used anticoagulant is WA, and most reports on anticoagulant-induced skin necrosis mention WA [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of breast necrosis remains unclear [1,2,5]. The sporadic nature of the condition cannot supply enough data on the this rare phenomenon [6].…”
Section: Introductionmentioning
confidence: 99%